Metal Concentrations in the Muscle of Male and Female Shrimp (Parapenaeus longirostris Lucas, 1846) Collected from Marmara Sea and Their Relationships with Season - CEVIK, FATMA; KENAN BAYHAN, YUSUF; BARIS DERICI, OSMAN (Asian Journal of Chemistry, 2010)
Seasonal variation of heavy metal concentrations (Zn, Fe, Mn, Cr and Cd) in muscle tissues of female and male specimens of economically important shrimp species, Parapenaeus longirostris, obtained from the Northeast of Kapidag Peninsula in the Marmara Sea (Turkey). For each season, 30 female and 30 male samples were analyzed by ICP-AES and AAS after wet digestion. According to the results of One-way ANOVA, concentrations of metals in muscle tissues were found to be significantly affected by the seasons. The pattern of the metal abundance in the muscle of both female and male shrimp can be written in descending order as follows: Zn > Fe > Mn > Cr > Cd. Concentrations of metals were all below the legislation limits.